Development of Grey Mildew Disease in Cotton as Influenced by Weather Parameters and its Management - Bhattiprolu, S. L.; Ratnam, M.; Kumari, S. Ratna (International Journal of Economic Plants, 2016)
The effect of weather factors on the development of grey mildew in susceptible Bt Cotton hybrid Jadoo BG II was investigated during kharif 2013-2014 in vertisols at Regional Agricultural Research Station, Lam, Guntur under rainfed conditions. Weekly data on disease score at different phenological stages of the crop was recorded on randomly labelled plants and per cent disease intensity (PDI) was correlated with weather parameters. Grey mildew appeared during 44th meteorological week at flowering stage and reached its peak (43%) during the 52nd meteorological week at boll maturity stage. Significant negative correlation was observed for maximum temperature and minimum temperature with per cent disease intensity. Multiple linear regression of PDI indicated that for every one per cent increase in evening relative humidity there was corresponding increase of 0.64 in per cent disease index of grey mildew spot and suggests preventive and / or protective measures are to be taken up with recommended fungicides like 0.3% wettable sulphur or 0.1% carbendazim.